2013
DOI: 10.4315/0362-028x.jfp-12-365
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Seven Different Commercially Available Real-Time PCR Assays for Detection of Shiga Toxin 1 and 2 Gene Subtypes

Abstract: Following the recent outbreak of Shiga toxin-producing Escherichia coli (STEC) O104:H4 infection in Germany, the demand for fast detection of STEC has again increased. Various real-time PCR-based methods enabling detection of Shiga toxin genes (stx) have been developed and can be used for applications in food microbiology. The present study was conducted to evaluate the reliability of seven commercially available real-time PCR systems for detection of stx1 and stx2 subtypes. For this purpose, pure cultures of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 9 publications
1
13
0
Order By: Relevance
“…Other studies also reported the failure of some PCR/qPCR assays to detect genetically distant stx subtypes, e.g., stx 2b , stx 2f , and stx 2g (40,45). A recent evaluation of seven commercially available qPCR systems for stx subtypes also returned variable results (41). Therefore, careful selection and evaluation of primers/ probes are critical in developing these NAATs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies also reported the failure of some PCR/qPCR assays to detect genetically distant stx subtypes, e.g., stx 2b , stx 2f , and stx 2g (40,45). A recent evaluation of seven commercially available qPCR systems for stx subtypes also returned variable results (41). Therefore, careful selection and evaluation of primers/ probes are critical in developing these NAATs.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have closely examined the ability of PCR and qPCR to detect STEC stx or eae subtypes (39)(40)(41), and to our knowledge, only one recent study explored the ability of LAMP to detect eae variants (42). There are currently 3 stx 1 subtypes (stx 1a , stx 1c , and stx 1d ), 7 stx 2 subtypes (a through g), and about 30 eae subtypes (␣, ␤, ␥, ε, etc.)…”
Section: Discussionmentioning
confidence: 99%
“…The Centers for Disease Control and Prevention guidelines from October 2009 recommend simultaneous culture of stool samples and detection of Shiga toxins and/or their genes for all STEC isolates (31). Amplification and enzyme immunoassay (EIA) kits for STEC detection are commercially available (30,(32)(33)(34).…”
mentioning
confidence: 99%
“…In contrast, the T m value of stx2f (81.729 C) was lower than those of stx2a, stx2b, stx2c, stx2d, and stx2e, and the T m value of stx2g (83.649 C) was slightly higher than those of stx2a, stx2b, stx2c, stx2d, and stx2e. Several real-time PCR assays for detection of stx1 and stx2 have been developed (8)(9)(10)(11), and real-time PCR assays using TaqMan probes, as reported by Derzelle et al (12), have been shown to detect all known stx2 subtypes. Nonetheless, real-time PCR with TaqMan probes is expensive as compared to that based on SYBR Green I (31).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the stx2 gene of enterohemorrhagic E. coli (EHEC) has recently been classified into 7 subtypes (stx2a, stx2b, stx2c, stx2d, stx2e, stx2f, and stx2g) (7). Although real-time PCR assays have been developed to detect these 7 stx2 subtypes (8)(9)(10)(11)(12), detection of these subtypes by RFBS24 has not yet been evaluated.…”
Section: Introductionmentioning
confidence: 99%